Change in Right Inferior Longitudinal Fasciculus Integrity Is Associated With Naming Recovery in Subacute Poststroke Aphasia. (September 2020) - Blom-Smink, Marieke; Verly, Marjolein; Spielmann, Kerstin; Smits, Marion; Ribbers, Gerard M.; van de Sandt-Koenderman, Mieke W. M. E.
Background . Despite progress made in understanding functional reorganization patterns underlying recovery in subacute aphasia, the relation between recovery and changes in white matter structure remains unclear. Objective . To investigate changes in dorsal and ventral language white matter tract integrity in relation to naming recovery in subacute poststroke aphasia. Methods . Ten participants with aphasia after left-hemisphere stroke underwent language testing and diffusion tensor imaging twice within 3 months post onset, with a 1-month interval between sessions. Deterministic tractography was used to bilaterally reconstruct the superior longitudinal fasciculus (SLF), inferior fronto-occipital fasciculus (IFOF), inferior longitudinal fasciculus (ILF), middle longitudinal fasciculus (MdLF), and uncinate fasciculus (UF). Per tract, the mean fractional anisotropy (FA) was extracted as a measure of microstructural integrity. Naming accuracy was assessed with the Boston Naming Test (BNT). Correlational analyses were performed to investigate the relationship between changes in FA values and change in BNT score. Results . A strong positive correlation was found between FA change in the right ILF within the ventral stream and change on the BNT ( r = 0.91, P < .001). An increase in FA in the right ILF was associated with considerable improvement of naming accuracy (range BNT change score: 12-14), a reduction with limited improvement or slight deterioration. No significant correlations were found between change in naming accuracy and FA change in any of the other right or left ventral and dorsal language tracts. Conclusions . Naming recovery in subacute aphasia is associated with change in the integrity of the right ILF.